2006
DOI: 10.1007/s11127-006-9112-2
|View full text |Cite
|
Sign up to set email alerts
|

The charitable activities of terrorist organizations

Abstract: Violent groups sometimes invest significant resources in social work, notably in the form of charities and NGOs. The present paper models a terrorist group's charities as a means to advertise its cause in order to raise popular support. The analysis explains how different types of organizations arise in equilibrium, depending on government policies. Then, the interaction between a purely terrorist group and an independent local NGO is examined. It is shown that a purely terrorist group always invests in more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Flanigan () concluded that this process generated community support for LTTE. Ly () examined organizations that perform charity work but also engage in violence. Ly () examined local NGOs that share values with a terrorist group and concluded that such terrorist groups benefit from the activities of NGOs without actually cooperating with them.…”
Section: Political Stability In Country Of Operationmentioning
confidence: 99%
“…Flanigan () concluded that this process generated community support for LTTE. Ly () examined organizations that perform charity work but also engage in violence. Ly () examined local NGOs that share values with a terrorist group and concluded that such terrorist groups benefit from the activities of NGOs without actually cooperating with them.…”
Section: Political Stability In Country Of Operationmentioning
confidence: 99%
“…Paul () argues that the provision of public goods by terrorist groups may also strengthen their popular support and thereby affect the level of terrorism a country experiences. Many terrorist groups (such as Hamas ) indeed also act as charitable organizations that provide social services in territory they control (Ly, ). Berman and Laitin () and Berman () argue that terrorist groups are particularly resilient and successful when they provide their members with vital “club goods,” while inhibiting free‐rider behavior.…”
Section: Evaluation Of Counterterrorism Strategiesmentioning
confidence: 99%
“…Other authors examined threshold or tipping points where rebellious action beyond a certain level becomes a self-generating process as there is safety in numbers (Kuran 1989(Kuran , 1991. Our approach is most closely akin to Ly's (2007), given that supporters maximize their welfare, while being constrained by a time and budget constraint. Unlike Ly (2007), we do not depict supporters as dividing their time between violent and charitable activities.…”
Section: Stage 3: Local Supporters Of the Terrorist Movementmentioning
confidence: 99%